PERAN ELON MUSK DALAM KONFLIK RUSIA-UKRAINA 2022 - Maulana, Muhammad Alfian (Indonesian Association for International Relations, 2024)
This paper analyzes the impact of entrepreneur and public figure Elon Musk on the 2022 Russia-Ukraine conflict. Through the use of social network theory and the concept of Popularity, this research shows that although Musk was not an official state actor, he played a significant role in the conflict. His global popularity and extensive connections to both sides of the conflict enabled him to influence the government, media, and public. His actions and statements, such as providing Ukraine with Starlink Internet access and proposing a controversial peace plan, had a visible impact on the dynamics of the conflict. These findings highlight the significant role and potential influence of non-state actors in international conflicts. Non-state actors, particularly those with global reach and popularity, can shape public opinion, influence government policies, and even alter the course of conflicts.